(untitled) (Research, Society and Development, 2024)
Objective: To analyze the clinical and epidemiological profile of patients hospitalized for pulmonary embolism in Brazil and its cost to the public sector. Methodology: A descriptive ecological study was conducted in January 2024 by analyzing data obtained from the Hospital Information System (SIH/SUS). Epidemiological and financial variables related to hospitalization for pulmonary embolism in Brazil between 2019 and 2023 were analyzed. Results and Discussion: A total of 55,439 cases of hospitalizations for PE were reported in Brazil during the analyzed period, with a notable increase in 2023. There was a discrepancy in the comparison of total hospitalization costs in all analyzed regions. The Southeast and South regions stood out regarding number of hospitalizations, total expenditures, and hospitalization rates per 100,000 inhabitants. The analysis of these variables reveals vast inequality in access to the healthcare system among Brazilian regions. Conclusion: The development of public policies for equity in hospital resources, standardization of medical procedures, and prevention of pulmonary embolism is crucial, along with the promotion of new research. This is expected to enhance healthcare by ensuring early diagnosis and timely treatment, aiming to reduce hospitalizations, length of stay, mortality, and public spending.